Relevansi Prinsip Pembelajaran Kurikulum Merdeka dengan Konsep Pendidikan Islam (Analisis terhadap Permendikbudristek No. 262/M/2022) - Efi Parinda; Sri Murhayati (IAIN Batusangkar, 2024)
This research aims to analyze the decision of the minister of education, culture, research and technology number 262/M/2022 on the independent curriculum regarding learning principles and their relevance to the concept of Islamic education. This research method is descriptive analysis of ministerial decisions, the concept of Islamic education according to Islamic education experts guided by the messages of the Prophet, previous research which contains the principles of learning. The results of the study stated that the Regulation of the Minister of Education, Culture, Research and Technology No. 262/M/2022 contains learning and assessment. The five principles contained in Decree number 262 / M / 2022 are learning designed by considering the stage of development, level of achievement of students, lifelong learning design, encouraging self-reflection and carried out holistically. Learning is designed and implemented to build the capacity of lifelong learners by encouraging them to do holistic reflection.┬á┬á